DO THE RADIOLOGICAL CRITERIA WITH THE USE OF RISK FACTORS IMPACT THE FORECASTING OF ABDOMINAL NEUROBLASTIC TUMOR RESECTION IN CHILDREN? - PENAZZI,Ana Cláudia Soares (2017)
ABSTRACT Background: The treatment of neuroblastoma is dependent on exquisite staging; is performed postoperatively and is dependent on the surgeon’s expertise. The use of risk factors through imaging on diagnosis appears as predictive of resectability, complications and homogeneity in staging. Aim: To evaluate the traditional resectability criteria with the risk factors for resectability, through the radiological images, in two moments: on diagnosis and in pre-surgical phase. Were analyzed the resectability, surgical complications and relapse rate. Methods: Retrospective study of 27 children with abdominal and pelvic neuroblastoma stage 3 and 4, with tomography and/or resonance on the diagnosis and pre-surgical, identifying the presence of risk factors. Results: The mean age of the children was 2.5 years at diagnosis, where 55.6% were older than 18 months, 51.9% were girls and 66.7% were in stage 4. There was concordance on resectability of the tumor by both methods (INSS and IDRFs) at both moments of the evaluation, at diagnosis (p=0.007) and post-chemotherapy (p=0.019); In this way, all resectable patients by IDRFs in the post-chemotherapy had complete resection, and the unresectable ones, 87.5% incomplete. There was remission in 77.8%, 18.5% relapsed and 33.3% died. Conclusions: Resectability was similar in both methods at both pre-surgical and preoperative chemotherapy; preoperative chemotherapy increased resectability and decreased number of risk factors, where the presence of at least one IDRF was associated with incomplete resections and surgical complications; relapses were irrelevant.